Expression and variability of lipid metabolism genes in intracranial aneurysm - Synowiec, E; Wojcik, K A; Wójcik, R; WiÅ›niewski, K; Fila, M; Tokarz, P; BieÅ„kowski, M; Jaskolski, D; Blasiak, J (Cellular and Molecular Biology, 2016)
The objective of this study was to investigate the association between mRNA expression and single nucleotide polymorphisms (SNPs) of the ATP-binding cassette transporter (ABCA1) gene, apolipoprotein A1 (APOA1) gene, low-density lipoprotein (LDLR) gene and RNA gene located in the CDKN2B-CDKN2A cluster (CDKN2B-AS1) involved in lipid metabolism and the occurrence of intracranial aneurysm (IA). Fifty three IA patients, and 27 controls (IA-free) were enrolled in this study and were genotyped for seven single nucleotide polymorphisms. Increased expression of the LDLR gene in IA patients was observed. The A/G genotype and the A allele of the c. –113G>A polymorphism of the APOA1 gene were associated with increased occurrence of IA (ORs 12.36 and 14.14, respectively), while the G/G genotype and G allele showed the opposite tendency (ORs 0.06 and 0.07, respectively). We also detected that the A/A–G/A combined genotype of the c. –113G>A – APOA1 and g.46859A>G – LDLR SNPs was associated with a decreased occurrence of IA. Moreover, the A/G–G/G combined genotype of the c.656G>A – ABCA1 and c. –113G>A – APOA1 was associated with a decreased occurrence of IA. The results of our study suggest the association between expression and variability of lipid metabolism genes and occurrence of IA.